2021
DOI: 10.1021/acsomega.0c02588
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical and Quantum Descriptor Calculations for Gaining Insight into Ricin Toxin A (RTA) Inhibitors

Abstract: In this work, we performed a study to assess the interactions between the ricin toxin A (RTA) subunit of ricin and some of its inhibitors using modern semiempirical quantum chemistry and ONIOM quantum mechanics/molecular mechanics (QM/MM) methods. Two approaches were followed (calculation of binding enthalpies, Δ H bind , and reactivity quantum chemical descriptors) and compared with the respective half-maximal inhibitory concentration (IC 50 ) experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…We used the BFGS algorithm for the full relaxation (both lattice and atomic position optimizations) of the crystal structure. Using the DFT-optimized structures, we calculated the lattice energies via the semiempirical PM7 method as implemented in MOPAC v2016 which has been shown to have good performance in predicting thermodynamic properties particularly for organic systems. , To validate the calculated lattice energies, we compared the experimental melting point against the melting point computed from the lattice energy using the simple model of Salahinejad et al This model assumes a linear relationship between the ratio of enthalpy of sublimation to the melting point (Δ H sub / T m ) against the number of rotatable bonds …”
Section: Methodsmentioning
confidence: 99%
“…We used the BFGS algorithm for the full relaxation (both lattice and atomic position optimizations) of the crystal structure. Using the DFT-optimized structures, we calculated the lattice energies via the semiempirical PM7 method as implemented in MOPAC v2016 which has been shown to have good performance in predicting thermodynamic properties particularly for organic systems. , To validate the calculated lattice energies, we compared the experimental melting point against the melting point computed from the lattice energy using the simple model of Salahinejad et al This model assumes a linear relationship between the ratio of enthalpy of sublimation to the melting point (Δ H sub / T m ) against the number of rotatable bonds …”
Section: Methodsmentioning
confidence: 99%
“…The generated unit cells were then optimized using the semiempirical PM7 Hamiltonian with periodic boundary conditions as implemented in MOPAC v2016, 29 , 30 which has been shown to have good performance in predicting thermodynamic properties particularly for organic systems. 31 , 32 The structures of the five most stable candidates were further refined using periodic density functional theory (DFT) calculations as implemented in the CP2K package, 33 which uses a mixed Gaussian/plane-wave (GPW) basis set. The exchange and correlation energies were evaluated using the semilocal Perdew–Burke–Ernzerhof (PBE) form of the generalized gradient approximation (GGA) functional together with Grimme’s D3 van der Waals correction.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the computational cost, we constrained the search space to the most common space groups for chiral cocrystals, i.e., P 1, P -1, P2, P 21, P 21/ c , and P 212121. The generated unit cells were then optimized using the semiempirical PM7 Hamiltonian with periodic boundary conditions as implemented in MOPAC v2016, , which has been shown to have good performance in predicting thermodynamic properties particularly for organic systems. , The structures of the five most stable candidates were further refined using periodic density functional theory (DFT) calculations as implemented in the CP2K package, which uses a mixed Gaussian/plane-wave (GPW) basis set. The exchange and correlation energies were evaluated using the semilocal Perdew–Burke–Ernzerhof (PBE) form of the generalized gradient approximation (GGA) functional together with Grimme’s D3 van der Waals correction. , DZVP-MOLOPT basis sets and Goedecker–Teter–Hutter (GTH) pseudopotentials were selected in the calculations. , An energy cutoff of 500 Ry and relative energy cutoff of 80 Ry were found to be sufficient for energy convergence.…”
Section: Methodsmentioning
confidence: 99%
“…1−5 However, due to the limitation of the experimental techniques, it is challenging to investigate other properties of the SEI like thermodynamics and kinetics of its formation and growth. [1][2][3]5,6 To fill this knowledge gap, computational models have emerged to better understand the SEI formation and growth. Previous theoretical studies (e.g., DFT) focused on the decomposition pathways of main electrolyte species, i.e., the ethylene carbonate solvent and the supporting salt lithium hexafluorophosphate, LiPF 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rocha-Santos et al have used PM6 and PM7 methods to gain insights into the binding energies of various ligand/protein complexes. 6 In the context of lithium-ion batteries, a study performed by Kim et al has compared the performance of various semiempirical methods based on the Hartree−Fock methods to investigate the electronic properties of various solvents used in lithium-ion batteries. 14 They found that PM#-based methods showed better agreement with DFT reference data.…”
Section: Introductionmentioning
confidence: 99%